The influence of direct democracy on the shadow economy - Désirée Teobaldelli; Friedrich Schneider (Johannes Kepler University of Linz, Department of Economics, 2013)
We analyze, both theoretically and empirically, the influence of direct democratic institutions on the size and development of shadow economies. Our model suggests that, as the extent of direct democracy increases, implemented fiscal policies more nearly reflect the preferences of citizens and so reduce their incentives to operate in the informal sector. This theory implies a negative relationship between the extent of direct democracy and the size of the country's shadow economy. We also theorize that direct democracy has a greater effect in reducing the informal sector when the former is at low or intermediate values and when the electoral system is characterized by a larger district magnitude. An empirical investigation of a sample of 57 democracies confirms our model's predictions.
Keywords: O17; P16; H11; H26; 330; shadow economy; direct democratic institutions; district magnitude; good governance